Productivity, markups, and reallocation: Evidence from French manufacturing firms from 1994 to 2016 - Enrico De Monte (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
This paper investigates the evolution of aggregate productivity and markups among French manufacturing firms between 1994 and 2016, by focusing on the role of reallocation with respect to both aggregate measures. Firm-level productivity and markups are estimated based on a gross output translog production function using popular estimation methods. I find an aggregate productivity growth of about 34% over the whole period while aggregate markups are found to remain relatively stable. As a key finding the study shows that over time reallocation of sales shares affects differently aggregate productivity and markups: Before 2000 both aggregate productivity and markups are importantly driven by reallocation effects; Post-2000, instead, the contribution of reallocation to aggregate productivity becomes negligible, inducing a slowdown in aggregate productivity growth, while I measure persistent reallocation of sales shares from lower to higher markup firms. Policy relevant implications of these dynamics are discussed.
Keywords: C13; D21; D24; L16; L60; O47; 330; productivity decomposition; production function estimation; business dynamism; market power; entry and exit